2019
DOI: 10.9740/mhc.2019.01.061
|View full text |Cite
|
Sign up to set email alerts
|

Propranolol for mirtazapine-induced akathisia: Single case report

Abstract: Despite psychomotor restlessness and akathisia being an occasionally reported side effect of antidepressants as a class, and mirtazapine specifically, there is no general consensus on the best treatment approach. Propranolol may prove to be an effective treatment approach in patients who are not candidates for alternative therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…In our case, a daily clonazepam dose of 2 mg was not efficacious in akathisia associated with mirtazapine use. However, in the treatment of akathisia associated with mirtazapine use, the efficacy of clonazepam, diazepam, and β-blockers has been reported by others 4–6 . Conversely, Markoula and coworkers 7 reported a case in which clonazepam was not efficacious, and in light of our case, clonazepam may not be efficacious in some patients.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…In our case, a daily clonazepam dose of 2 mg was not efficacious in akathisia associated with mirtazapine use. However, in the treatment of akathisia associated with mirtazapine use, the efficacy of clonazepam, diazepam, and β-blockers has been reported by others 4–6 . Conversely, Markoula and coworkers 7 reported a case in which clonazepam was not efficacious, and in light of our case, clonazepam may not be efficacious in some patients.…”
Section: Discussionmentioning
confidence: 48%
“…[1][2][3] Conversely, it has been suggested that mirtazapine may be associated with akathisia if given at a high dose because of blockade of presynaptic a2-adrenergic receptors. 4 There have been several case reports of mirtazapine associated with akathisia, all using a daily dose ≥15 mg. [4][5][6][7] Mirtazapine has been postulated to work therapeutically against akathisia at low (15 mg) and very low (7.5 mg) daily doses, 1,3 with no reports of akathisia occurring at a daily dose <15 mg. We report a case of continued akathisia even with a very low daily dose (7.5 mg) of mirtazapine, which differs from findings from previous studies.…”
mentioning
confidence: 99%
“…(13). In a recent case report, a 30-year-old male patient who developed akathisia after mirtazapine use was presented, and the findings suggested that propranolol treatment was beneficial (14). In our case, akathisia was observed after adding 15 mg/day mirtazapine to the treatment of the patient who has been using fluoxetine for six months.…”
Section: Discussionmentioning
confidence: 48%
“…The woman developed pancreatitis; therefore, MIRT was discontinued as the probable reason for her hypertriglyceridemia-induced pancreatitis ( Bowers et al, 2019 ). The side effects of MIRT, including psychomotor restlessness and akathisia, are described as warnings, which affect<1 % of the populace ( Koller, 2019 ).…”
Section: Discussionmentioning
confidence: 99%